2019
DOI: 10.1093/dote/doz056
|View full text |Cite
|
Sign up to set email alerts
|

Loss to follow-up after food impaction among patients with and without eosinophilic esophagitis

Abstract: SUMMARY Symptoms of esophageal dysfunction such as food impaction are consistent with, but not diagnostic for eosinophilic esophagitis (EoE) without obtaining histology. We conducted a retrospective study to characterize patients with food impaction at a tertiary center. We hypothesized that many patients with food impaction may be lost to follow-up and that many have features suggestive of EoE. Adult patients presenting to the emergency department with esophageal food impaction were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 12 publications
5
21
0
Order By: Relevance
“…14 Approximately 50% of patients who present on an emergency basis with an esophageal food impaction requiring endoscopic removal have EoE. 15,16 In patients with EoE, longer periods of untreated inflammation are associated with a higher prevalence of esophageal fibrosis, dysphagia, and food impaction. 17 A cohort study of 721 patients with EoE from the Netherlands reported that in patients with symptoms of EoE for more than 21 years at the time of diagnosis, the proportions of patients with strictures and esophageal food impactions were 52% and 57%, respectively.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…14 Approximately 50% of patients who present on an emergency basis with an esophageal food impaction requiring endoscopic removal have EoE. 15,16 In patients with EoE, longer periods of untreated inflammation are associated with a higher prevalence of esophageal fibrosis, dysphagia, and food impaction. 17 A cohort study of 721 patients with EoE from the Netherlands reported that in patients with symptoms of EoE for more than 21 years at the time of diagnosis, the proportions of patients with strictures and esophageal food impactions were 52% and 57%, respectively.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…43 Finally, in patients presenting as an emergency with food bolus obstruction, if biopsies were not taken, 79% were lost to secondary care follow-up, missing the opportunity to diagnose EoE. 44 Furthermore, in patients who have not had biopsies taken on their index endoscopy when presenting with a food-bolus obstruction, in those in whom a repeat endoscopy can be organised, there is a delay to diagnosis and follow-up of at least 2 years. 38 Biopsy at the time of endoscopy for food bolus obstruction is not associated with an increased risk of oesophageal perforation.…”
Section: Oesophageal Biopsies Should Be Taken At Index Endoscopy In P...mentioning
confidence: 99%
“…In a more recent study, 55% of patients with food bolus obstruction did not have biopsies taken at endoscopy during their first presentation and of those who were biopsied, insufficient biopsies to reliably exclude EoE were taken in 66% of patients 43. Finally, in patients presenting as an emergency with food bolus obstruction, if biopsies were not taken, 79% were lost to secondary care follow-up, missing the opportunity to diagnose EoE 44. Furthermore, in patients who have not had biopsies taken on their index endoscopy when presenting with a food-bolus obstruction, in those in whom a repeat endoscopy can be organised, there is a delay to diagnosis and follow-up of at least 2 years 38…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Failure to obtain biopsy samples at the time of impaction necessitates performing an additional endoscopy, which further delays confirmation of the diagnosis and medical treatment with the risk of losing these patients in follow-up. 57 Nevertheless, clinical situations such as patient instability or fear of aspiration during endoscopy may not allow the needed time to procure esophageal biopsy samples.…”
Section: Endoscopic Diagnosis: Biopsymentioning
confidence: 99%